Analisis Pemberitaan Sengketa Lahan Stain Teungku Dirundeng Meulaboh - Junaidi; Ismail Arafah; Nurhazizah (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2021)
The focus of this research is on the news of how AJNN.net informs the Controversy Area of Sekolah Tinggi Agama Islam Negeri Teungku Dirundeng Meulaboh. To find out the content of the news text and how the message in the text is conveyed through the discourse constructed on the news, the author uses descriptive qualitative methods. To get some conclusion clear, intimately close and critical conclusions, some of the news in the media were analyzed using discourse analysis theory by Teun Van Dijk. there are six (6) elements of analysis that the author uses to review the news that has been selected. The results found that during the conveyed news, the AJNN reporter did not convey the news in equal manner. The news was found without containing information verification from both informants (cover both sides).